Nexus between trade and environmental quality in sub-saharan Africa: Evidence from panel GMM - Andriamahery, Anselme; Danarson, Jules Harris; Qamruzzaman, Md (Frontiers in Environmental Science, 2022)
Environmental sustainability is a burning facts in across the world especially for the developing nations. Equitable economic development, environmental protection, energy efficiency and energy security has placed the apex state in economic discussant and policy formulation. This paper establishes the relationship between trade and environmental quality in Sub-Saharan Africa (SSA). Following the Environmental Kuznets Curve (EKC) theory, we investigate the existence of an inverted U-shape correlation between income per capita growth and nitrous oxide (N2O), agricultural methane (ACH4), and carbon dioxide (CO2) emissions to ascertain the presence of EKC. We also analyze how to trade variables, income per capita growth, energy intensity, foreign direct investment, human capital, and CO2 emissions are related. The results show that trade significantly increases N2O, ACH4, and CO2 emissions for the overall sample of SSA and its income groups [Upper-Middle-Income Countries (UMIC), Lower-Middle-Income Countries (LMIC), and Low-Income Countries (LIC)] using a panel GMM. This paper concludes that reducing emissions is feasible in the future as shown by the existence of the EKC, and trade has a consistently negative impact on the environment in SSA countries, regardless of wealth level. On the policy note, study suggested the domestic trade liberalization and foreign ownership in the economy play an detrimental role and thus industrialization have to ensure with energy efficiency and energy security.